2019
DOI: 10.1111/meca.12253
|View full text |Cite
|
Sign up to set email alerts
|

House prices and immovable property tax: Evidence from OECD countries

Abstract: This paper studies the impact of changes in immovable property tax revenues on the growth rate of house prices by analysing a panel of 34 OECD countries over the period 1970–2014. Starting from the annual series of immovable property tax revenues, we isolate years of significant shifts in the property tax regime and study their impact on house prices. We find a strong negative relationship between increases in immovable property tax revenues and house prices. This relationship is robust to the inclusion of cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Moreover, buyers will make a trade-off between house prices and public services, and property taxes may increase the house prices by funding public spending (Arik, 2021 ; Carrillo et al, 2021 ). Other researchers have reported that property taxes can effectively decrease house prices (Angjellari-Dajci et al, 2015 ; Oliviero et al, 2019 ; Bø, 2020 ; Li et al, 2020 ; Zhu and Johnson, 2020 ; Giertz et al, 2021 ). The capitalization equation clearly illustrates the mechanism underlying this effect:…”
Section: Literature Institutional Background and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, buyers will make a trade-off between house prices and public services, and property taxes may increase the house prices by funding public spending (Arik, 2021 ; Carrillo et al, 2021 ). Other researchers have reported that property taxes can effectively decrease house prices (Angjellari-Dajci et al, 2015 ; Oliviero et al, 2019 ; Bø, 2020 ; Li et al, 2020 ; Zhu and Johnson, 2020 ; Giertz et al, 2021 ). The capitalization equation clearly illustrates the mechanism underlying this effect:…”
Section: Literature Institutional Background and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies have adopted various approaches to determine the influence of taxation on house price volatility. Most studies have used policies related to transaction or retention links of housing and aggregate national-scale data to assess policy implications on housing prices [56,57]. In addition, they have either framed the analysis in the context of market distortion [47,49,52,58,59], analyzing investment behavior [60,61], or cost-value analysis [62,63].…”
Section: Real Estate Taxes and House Pricesmentioning
confidence: 99%
“…Many empirical studies have indicated that both transaction and transfer links have significant explanatory power for price differences before and after the implementation of taxes. However, limited studies [57,64] have adopted the aggregate impact of both forms of tax policies and have analyzed price variation between cities. Furthermore, national-and provincial-scale aggregate data, ignoring intercity demand and supply heterogeneity, will limit the strength of a conclusion [53,65].…”
Section: Real Estate Taxes and House Pricesmentioning
confidence: 99%
See 1 more Smart Citation